Professor O.M. Kowalewski—Mongolian studies scholar, traveller and enlightener: His biographical landmarks - Valeev, Ramil M. M.; Kulganek, Irina V. V.; Tulisow, Jerzy (Acta Orientalia Vilnensia, 2009)
Kazan (Volga Region) Federal UniversityInstitute of Oriental Manuscripts of Russian Academy of ScienceUniversity of Warsaw In this article, materials devoted to the basic stages of the life and activity of a graduate of Vilna University (1821), Professor Osip Mikhailovich Kowalewski (1801–1878), are presented. He held the first chair of Mongolian literature in Russia and Europe and served as dean and rector of Kazan University. Prof Kowalewski made scientific trips to Siberia, Buryatia, Mongolia and China (1828–1833); collected unique books, manuscripts, and ethnographic materials of the people of Central Asia; and became the author of classical works concerning Buddhism and the history, languages, literature, religions, folklore, and ethnography of the Mongolian people.